2014
DOI: 10.1016/j.febslet.2014.03.037
|View full text |Cite
|
Sign up to set email alerts
|

miR‐181a mediates metabolic shift in colon cancer cells via the PTEN/AKT pathway

Abstract: a b s t r a c tCancer cell metabolism is often characterized by a shift from an oxidative to a glycolytic bioenergetics pathway, a phenomenon known as the warburg effect. Whether the deregulation of miRNAs contributes to the warburg effect remains largely unknown. Here we show that miR-181a expression is increased and thus induces a metabolic shift in colon cancer cells. miR-181a performs this function by inhibiting the expression of PTEN, leading to an increase of phosphorylated AKT which triggers metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 19 publications
4
57
1
1
Order By: Relevance
“…miR-181a mediates metabolic shift in colon cancer cells via the PTEN/ AKT pathway. 29 In this study, we found that miR-181a directly targeted 3′UTR of PTEN and luciferase report assay verified that PTEN is a target gene of miR-181a. The tumor suppressor PTEN is a phosphatase with sequence similarity to the cytoskeletal protein tensin.…”
Section: Discussionsupporting
confidence: 51%
“…miR-181a mediates metabolic shift in colon cancer cells via the PTEN/ AKT pathway. 29 In this study, we found that miR-181a directly targeted 3′UTR of PTEN and luciferase report assay verified that PTEN is a target gene of miR-181a. The tumor suppressor PTEN is a phosphatase with sequence similarity to the cytoskeletal protein tensin.…”
Section: Discussionsupporting
confidence: 51%
“…5a). Accumulating evidence has demonstrated that PTEN-Akt signaling pathway is tightly associated with the occurrence and development of a variety of tumors [31][32][33]; further investigation in the current study showed that WWP1 depletion increased PTEN level and reduced p-Akt level in MKN-45 and AGS cells but did not change total Akt level in MKN-45 and AGS cells (Fig. 5b-e).…”
Section: Wwp1 Downregulation Inactivated Pten-akt Signaling Pathwaysupporting
confidence: 52%
“…Over the last decade, many miRNAs have been showed in regulating diverse biological events such as cell proliferation, differentiation and apoptotic processes [5][6][7], which are important in the development of cancer. Accumulated evidence indicated that aberrant expression of miRNAs associates with various types of cancer.…”
Section: Aimmentioning
confidence: 99%